Occupational Stress and Burnout in the Fire Service: Examining the Complex Role and Impact of Sleep Health. Issue 2 (March 2022) - Dyal, Mari-Amanda A.; Smith, Todd D.; DeJoy, David M.; Moore, Brian A.
The occupational stress inherent in firefighting poses both physiological and psychological risks to firefighters that have been found to possess a reciprocal nature. That is, the nature of these relationships in terms of indicator and impact are elusive, especially as it relates to sleep health (e.g., quality, quantity, hygiene, etc.) as a specific physiological risk and burnout as a specific psychological risk. A series of mediation models were assessed to examine the reciprocal relationships between occupational stress, burnout, and sleep health in a sample of 161 career firefighters. The mediation models confirmed reciprocity among the variables in so much that relationships were best described by the underlying mechanism at work. Comprehensive assessments of both subjective and objective markers of sleep health should be incorporated into firefighter research to supplement behavioral health assessments and interventions, especially related to burnout and occupational stress.